Property in East Central Europe : notions, institutions, and practices of landownership in the twentieth century - Siegrist, Hannes; Müller, Dietmar, 1969- (Berghahn Books, 2015)
Property is a complex phenomenon comprising cultural, social, and legal rules. During the twentieth century, property rights in land suffered massive interference in Central and Eastern Europe. The promise of universal and formally equal rights of land ownership, ensuring predictability of social processes and individual autonomy, was largely not fulfilled. The national appropriation of property in the interwar period and the communist era represent an onerous legacy for the postcommunist (re)construction of a liberal-individualist property regime. However, as the scholars in this collection.